2016
DOI: 10.1186/s40733-016-0026-6
|View full text |Cite
|
Sign up to set email alerts
|

Asthma phenotypes: the intriguing selective intervention with Montelukast

Abstract: Asthma is a heterogeneous disease, usually characterized by chronic airway inflammation and a variable course associated with various underlying mechanisms that can differ between individuals. Patients with asthma can therefore exhibit different phenotypes, a term used to define the observable characteristics of an organism resulting from the interaction between its genetic makeup and the environment. The heterogeneity of asthma has received a large amount of attention in the last few years in order to better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 119 publications
0
15
0
1
Order By: Relevance
“…Blockers of CysLT 1 , including montelukast (marketed as Singulair and Kipres), pranlukast (Onon), and zafirlukast (Accolate), are used in asthma and rhinitis. Montelukast, which is administered orally once daily, is the most prescribed antagonist for asthmatic patients (176). This drug is effective in allergic rhinitis and several types of asthma, e.g., exerciseinduced asthma, asthma in obese patients, asthma in smokers, and aspirin-induced asthma (176,177).…”
Section: Clinical Studies On Cyslt Receptor-targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Blockers of CysLT 1 , including montelukast (marketed as Singulair and Kipres), pranlukast (Onon), and zafirlukast (Accolate), are used in asthma and rhinitis. Montelukast, which is administered orally once daily, is the most prescribed antagonist for asthmatic patients (176). This drug is effective in allergic rhinitis and several types of asthma, e.g., exerciseinduced asthma, asthma in obese patients, asthma in smokers, and aspirin-induced asthma (176,177).…”
Section: Clinical Studies On Cyslt Receptor-targeted Therapymentioning
confidence: 99%
“…Montelukast, which is administered orally once daily, is the most prescribed antagonist for asthmatic patients (176). This drug is effective in allergic rhinitis and several types of asthma, e.g., exerciseinduced asthma, asthma in obese patients, asthma in smokers, and aspirin-induced asthma (176,177). The beneficial effect of montelukast in cardiovascular disease has been under clinical trial (178)(179)(180).…”
Section: Clinical Studies On Cyslt Receptor-targeted Therapymentioning
confidence: 99%
“…CysLTs are linked with the pathogenesis of asthma. As an important anti-leukotriene compound, montelukast has displayed its efficacy and safety profile in different age teams with asthma [16]. Montelukast has a significant inhibitory effect against bronchoconstriction caused by leukotriene D4 [17].…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review published this year concluded that the addition of LTRAs reduces moderate and severe exacerbations and improves lung function and asthma control compared with the same dose of ICSs but that the evidence does not support this class of controller therapy as an ICS-sparing agent [ 74 ]. LTRAs may be useful in particular situations, including those intolerant of or unwilling to use ICSs and those with allergic rhinitis, aspirin-induced asthma, viral-induced wheezing, and asthma in the elderly [ 1 , 75 ]. Data from a randomized, but unblinded, study of 297 patients on budesonide (400 μg/day) found that a 6-month trial of add-on montelukast safely improved FEV1, SGRQ, and rescue medication use at a faster rate than add-on doxofylline or tiotropium [ 76 ].…”
Section: Further Perspectivesmentioning
confidence: 99%